ESTABLISHING THE AVERAGE EFFECTIVE DOSE OF 2-HYDROXY-N-NAPHTHALENE-1-IL-2-(2-OXO-1,2-DIHYDRO-INDOL-3-YLIDENE)-ACETAMIDE AT THE «PUNISHABLE BEHAVIOR» MODEL - R.V. Lutsenko; A.G. Sydorenko; N.O. Vlasenko; O.A. Lutsenko (Проблеми екології та медицини, 2022)
Derivatives of 2-oxoindoline demonstrate significant biological and pharmacological activity, including diuretic, anti-inflammatory, antitumor, antiviral, antibacterial, analgesic, sedative, anticonvulsant and other effects. The aim of this research is to establish the average effective dose of 2-hydroxy-n-naphthalene-1-yl-2-(2-oxo-1,2-dihydro-indol-3-ylidene)-acetamide (compound 18) as a potential anxiolytic, as well as its therapeutic index. Materials and methods of research. The experiments were performed on 36 albino adult male Wistar rats. The average effective dose (ED50) of compound 18 for anxiolytic activity was investigated in the «punishable behavior» test. Rats were divided into 6 groups of 6 animals each. The dose range for the intraperitoneal route of administration was (1, 3, 6; 12, 24, 48 mg/kg). Results and discussion. The «punishable behavior» model, Vogel variant, determined the average effective dose (ED50) and dose-response relationship for 2-hydroxy-n-naphthalene-1-yl-2-(2-oxo-1,2-dihydro-indol-3-ylidene)-acetamide (compound 18) with a single intraperitoneal injection. Analysis of the results shows that the maximum dose that did not cause the effect was 1.0 mg/kg, the minimum effective dose ED16 was 4.5 mg/kg, and the maximum effective dose ED100 was 48 mg/kg. Conclusion. Experimentally determined ED50 of compound 18 in rats when administered intraperitoneally in the «punishable behavior» test, variant Vogel, was 11.9±2.85 mg/kg. The ED50 confidence margins were (4.92÷18.9) mg/kg. According to the therapeutic index, substance 18 exceeds diazepam by 14.8 times.